Clean living behavior to support optimal growth and development for children in Simalungun Regency - Siregar, Suri Mutia; Meutia, Amalia; Sinulingga, Samerdanta; Marlina, Lisa (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
Nagori Parik Sabungan is a village located in Dolok Pardamean District, Simalungun Regency. The location of the village is located within the coverage area of Lake Toba, so it has the potential to develop into a tourist destination village. However, this village still has several obstacles to develop tourism, one of which is the low awareness of the community to handle waste properly. This service aims to shape the behavior of LISA (See Garbage Take) in 100 children at the Nagori Parik Sabungan Nature School, so that it can help improve environmental hygiene in the village area and instill clean habits in children. Formation of LISA behavior is done by modifying economic token type behavior. An economic token is a method in which a person or group of people can get a token every time he displays the desired behavior. The series of service activities was held for approximately 29 days. As a result, 50% of participants children already understand the adverse effects of improper waste management, and 100% of child participants are able to display LISA behavior during the activity